Rastreamento e detecção precoce de doença aterosclerótica em pacientes com HIV positivo - Salmazo, Pericles Sidnei [UNESP] (2014)
Background: AIDS as well as atherosclerosis are important public health problems. The longer survival among HIV-infected is associated to increased number of cardiovascular events in this population and this association is not fully understood. Objectives: To identify the frequency of subclinical atherosclerosis in HIV-infected patients, compared with control subjects; to analyze the association of atherosclerosis with viral load, CD4 counts and antiretroviral treatment, cardiovascular risk factors and with the Framingham risk score, in HIV-positive patients. Methods: a prospective, cross-sectional, case-control study assessed the presence of subclinical atherosclerosis in 264 HIV-infected patients and 279 control subjects. Clinical evaluation included carotid intima-media thickness (IMT) measurement, the presence of plaque in the carotid arteries, arterial stiffness by pulse wave velocity (PWV) and augmentation index (AIx), blood levels of hs-CRP, lipids, glucose, albumin, blood count, urea, creatinine and cardiovascular risk according to Framingham risk score criteria. Results: Patients were six years older than controls (43.2±10.5 vs. 37.9±11.5 years; p<0.001). Also presented lower prevalence of overweight / obesity (51.1 vs 63.1%; p=0.005) and higher frequency of active smoking (43.6 vs. 16.1%; p<0.001). Plaques were found in 37% of patients in the HIV group and 4% in the control group (p<0.001). Patients with carotid plaque were on average 11 years older than those without plaques (51.4±9.21 vs. 40.2±9.40 years; P<0.001) and had higher fasting glucose [90 (78, 100) vs. 83 (76.5, 90) mg/dl; p=0.012], total cholesterol [200 (178, 244) vs. 181 (156, 208.5) mg/dL; p<0.001], LDL-c [120.1 (96.2, 148.4) vs. 96.8 (80, 125) mg/dL; p<0.001] and triglycerides [188.5 (125.5, 288.5) vs. 150.5 (108, 226) mg/dL; p=0.010], mean systolic blood pressure 10 mmHg higher (132±21 vs. 121±16 mmHg; p<0.001) and mean diastolic blood pressure 6 mmHg ...